Bacterial contamination of beef in Kota Bharu and surrounding provinces (2011) - Imad Ibrahim Ali Al-Sultan; Fazlina,F.; M.S. Muhammad; Jasbir.S (2012)
This investigation compares 42 beef samples obtained from Kota Bharu Government Abattoir (n=10), Pasir Mas Government Abattoir (n=9) and from various backyard slaughterhouses in Kota Bharu and surrounding provinces (n=23). The total plate count (TPC) and coliform count conducted on the samples were found to be significantly different (P < 0.05) between the 3 different locations. The samples from backyard slaughterhouses had consistently the higher TPC and coliform count. Some of the beef samples from backyard slaughterhouses were above the maximum limits of TPC (<1.0 x 106 cfu/g) as required by Malaysian regulatory standards under the Food Regulations (1985) and most of them exceeded the acceptable limits for coliform count (1000 mpn/g). There were isolates of some bacteria (Staphylococcus aureus, Salmonella sp., Streptococcus sp. and Escherichia coli) obtained from the beef samples. The study demonstrates that beef from backyard slaughterhouses is significantly poorer in meat hygiene standards as compared to beef from cattle slaughtered in government abattoirs and this may be of public health importance.